2023
DOI: 10.3389/fvets.2023.1167594
|View full text |Cite
|
Sign up to set email alerts
|

Bovine sperm HSP-70 molecules: a potential cryo-tolerance marker associated with semen quality and fertility rate

Abstract: IntroductionFreezability is the ability of sperm to maintain its vitality and quality from various stress during the cryopreservation process, which is very important for the success of fertilization in AI programs. Heat shock proteins (HSPs) are unique proteins induced in response to various stress, including excess reactive oxygen species (ROS) and oxidative damage to intracellular enzymes that can harm cells. This study aimed to analyze the potential of HSP-70 molecules in bovine sperm as a marker of freeza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 44 publications
0
1
1
Order By: Relevance
“…Correlation test results between the HSP70 gene or protein and semen quality parameters did not show a strong relationship. It is different from previous studies, which found that there is a close relationship between HSP70 and motility ( Pardede et al, 2023 ; Zhang et al, 2015a ; Hung et al, 1998 ), sperm morphological defects ( Huang et al, 2000 ), acrosome integrity ( Kamaruddin et al, 2004 ), and DNA fragmentation ( Rajoriya et al, 2014 ). Varghese et al (2016) also reported that there was a significant (P<0.05) decrease in HSP70 levels before freezing and after thawing.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…Correlation test results between the HSP70 gene or protein and semen quality parameters did not show a strong relationship. It is different from previous studies, which found that there is a close relationship between HSP70 and motility ( Pardede et al, 2023 ; Zhang et al, 2015a ; Hung et al, 1998 ), sperm morphological defects ( Huang et al, 2000 ), acrosome integrity ( Kamaruddin et al, 2004 ), and DNA fragmentation ( Rajoriya et al, 2014 ). Varghese et al (2016) also reported that there was a significant (P<0.05) decrease in HSP70 levels before freezing and after thawing.…”
Section: Discussioncontrasting
confidence: 91%
“…The primer sequences used for HSP70 gene expression analysis (NM_174344.1) were forward 5'-TTGGGGACAAGTCAGAGAATG-3' and reverse 5'-ATCGTGGGGTTCCTTTTGATG-3'. The HSP70 primer was obtained from literature studies where this primer has been applied and used on local bull breeds, such as Qinchuan ( Bos taurus ) ( Zhang et al, 2015a ), Madura ( Bos javanicus x Bos indicus ) ( Rosyada et al, 2023b ), and Bali ( Bos sondaicus ) ( Pardede et al, 2023 ) bulls. PPIA (NM_178320.2) was used as an endogenous control, with the primary sequence being forward 5'-ATGCTGGCCCCAACACAA-3' and reverse 5'-CCCTCTCACCTTGCCAAA-3'.…”
Section: Methodsmentioning
confidence: 99%